2022
DOI: 10.1177/09544119221074582
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing for hip head-neck taper tribocorrosion: A review of experimental methods

Abstract: In vitro test methods are challenged by the multi-factorial nature of head-neck taper connection tribocorrosion due to the consequences of simplification. Incorrect study design and misinterpretation of results has led to contradictory findings regarding important factors affecting head-neck taper tribocorrosion. This review seeks to highlight important considerations when developing in vitro test methods, to help researchers strengthen their study design and analyze the implications of others’ design decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…When considering these two studies, a particular limitation of the finite element method becomes clear. It is a simulative research method that is dependent on the parameter definitions and therefore makes it fundamentally difficult to compare different studies [36]. In this context, the data collected in the present study showed contradictory results.…”
Section: Discussionmentioning
confidence: 58%
“…When considering these two studies, a particular limitation of the finite element method becomes clear. It is a simulative research method that is dependent on the parameter definitions and therefore makes it fundamentally difficult to compare different studies [36]. In this context, the data collected in the present study showed contradictory results.…”
Section: Discussionmentioning
confidence: 58%